The Degeneration and Apoptosis Patterns of Cone Photoreceptors in rd11 Mice - Hua Zhang; Xia Li; Xufeng Dai; Juanjuan Han; Yangyang Zhang; Yan Qi; Ying He; Yan Liu; Bo Chang; Ji-jing Pang (Journal of Ophthalmology, 2017)
The retinal degeneration 11 (rd11) mouse is a new animal model with rapid photoreceptor degeneration. The long-term efficacy of gene therapy has a direct relationship with the onset of photoreceptor degeneration or apoptosis, whereas the degeneration or apoptosis patterns of photoreceptors are still unclear in rd11 mice. The distribution patterns of cone function-related L- and S-opsin were examined by immunofluorescence staining, and the apoptosis was performed by TUNEL assay in rd11 mice. The expression pattern of L-opsin or S-opsin in rd11 retina at postnatal day (P) 14 was similar to the pattern observed in wildtype retina. With increasing age, the expression of L-opsin and S-opsin, especially S-opsin, decreased significantly in rd11 mice. The degeneration of L-opsin began around the optic nerve and expanded to the periphery of the retina, from the ventral/nasal to dorsal/temporal retina, whereas the expression of S-opsin gradually decreased from the dorsal/temporal to ventral/nasal retina. Apoptotic signal appeared at P14 and was strongest at P28 of rd11 mice. The key genes associated with apoptosis confirmed those changes. These indicated that the degeneration and apoptosis of cone photoreceptors began at P14 of rd11 mice, which was a key point for gene therapy.